Basic managerial skills for all - McGrath, E.H. (New Delhi : Prentice-Hall, 1989)
The emphasis in this book is on the very basic and perfectible skills of management and leadership: reading, writing, learning, speaking, listening, being 'real', negotiating, teaching, training, and managing.
Includes bibliographical footnotes.
opc 30/12/2016, rua 06/03/2017
Loans
Keywords: Management